Periodontal disease and chronic kidney disease among Aboriginal adults; an RCT. Issue 1 (December 2015) - Jamieson, Lisa; Skilton, Michael; Maple-Brown, Louise; Kapellas, Kostas; Askie, Lisa; Hughes, Jaqui; Arrow, Peter; Cherian, Sajiv; Fernandes, David; Pawar, Basant; Brown, Alex; Boffa, John; et al.
Abstract Background This study will assess measures of vascular health and inflammation in Aboriginal Australian adults with chronic kidney disease (CKD), and determine if intensive periodontal intervention improves cardiovascular health, progression of renal disease and periodontal health over a 24-month follow-up. Methods The study will be a randomised controlled trial. All participants will receive the periodontal intervention benefits, with the delayed intervention group receiving periodontal treatment 24 months following baseline. Inclusion criteria include being an Aboriginal Australian, having CKD (a. on dialysis; b. eGFR levels of <60 mls/min/1.73 m2 (CKD Stages 3 to 5); c. ACR ≥30 mg/mmol irrespective of eGFR (CKD Stages 1 and 2); d. diabetes plus albuminuria (ACR ≥ 3 mg/mmol) irrespective of eGFR), having moderate or severe periodontal disease, having at least 12 teeth, and living in Central Australia for the 2-year study duration. The intervention involves intensive removal of dental plaque biofilms by scaling, root-planing and removal of teeth that cannot be saved. The intervention will occur in three visits; baseline, 3-month and 6-month follow-up. The primary outcome will be changes in carotid intima-media thickness (cIMT). Secondary outcomes will include progression of CKD or death as a consequence of CKD/cardiovascular disease. Progression of CKD will be defined by time to the development of the first of: (1) new development of macroalbuminuria; (2) 30 % loss of baseline eGFR; (3) progression to end stage kidney disease defined by eGFR <15 mLs/min/1.73 m2 ; (4) progression to end stage kidney disease defined by commencement of renal replacement therapy. A sample size of 472 is necessary to detect a difference in cIMT of 0.026 mm (SD 0.09) at the significance criterion of 0.05 and a power of 0.80. Allowing for 20 % attrition, 592 participants are necessary at baseline, rounded to 600 for convenience. Discussion This will be the first RCT evaluating the effect of periodontal therapy on progression of CKD and cardiovascular disease among Aboriginal patients with CKD. Demonstration of a significant attenuation of CKD progression and cardiovascular disease has the potential to inform clinicians of an important, new and widely available strategy for reducing CKD progression and cardiovascular disease for Australia's most disadvantaged population. Trial registration This trial is registered with the Australian New Zealand Clinical Trial RegistryANZCTR12614001183673 .